From 8-K to Deal Cards: A Source-Grounded Visual Triage Framework for FinTech M&A Filings (International Journal of Graphic Design, 2026)
Form 8-K is a timely public channel through which U.S. registrants disclose material events, including acquisition agreements, completed transactions, shareholder communications, and related exhibits. The density of this filing stream creates a visual communication problem: analysts need to identify source-linked deal cues without losing the legal and temporal provenance of each record. This study presents a source-grounded deal-card workflow for FinTech M&A filing triage. The analysis used the official SEC quarterly master indexes and included 16,439 Form 8-K and 8-K/A filings in Q4 2025, together with 276,261 contextual records in the complete Q4 index. Symmetric companion-form windows were protected against quarter-boundary truncation with the last 14 days of Q3 2025 and the first 14 days of Q1 2026. A seven-day window identified 222 rule-defined FinTech M&A targets across 94 company names, or 1.35% of the Q4 corpus. In five-fold cross-validation grouped by CIK, text-only logistic triage reached F1 = 0.224 and M&A-context logistic triage reached F1 = 0.322. Integrated logistic and linear SVM configurations reproduced the rule-defined target exactly (F1 = 1.000). Because the target was constructed from the same FinTech and M&A-neighborhood cues available to those configurations, this exact agreement is interpreted as rule-consistency validation rather than predictive superiority. A structural interface audit found that the deal-card schema exposed 10 documented fields, nine visual anchors, and six configured decision cues. These author-defined attributes describe interface structure; they do not measure comprehension, trust, or review speed. The contribution is a method for organizing SEC filing evidence for subsequent visual review.